Chinese Netizens’ Perception of Nepalese Social Life through WeChat Short Videos: A Cultivation Theory Perspective - Lawoju, Niraj (Bagiswori Journal, 2026)
Short videos in digital social media are shaping public opinion and perception about individuals and events today. They are widening international communication and subsequently affecting state-to-state and people-to-people relations. This qualitative research intends to explore the representation of Nepali life and culture in short videos posted in WeChat and how these digital contents are shaping the understanding about Nepal and Nepali people among Chinese netizens. For that, total 512 comments commented on 52 short videos posted by 12 WeChat accounts collected for purposeful sampling are studied as a primary data on the background of ‘World Syndrome perspective of the Cultivation Theory’ developed by George Gerbner. This study aims to answer two questions- 1) How Chinese WeChat users are understanding Nepal and Nepali social life through WeChat short videos? and 2) How image-shaping about Nepal and Nepali society among Chinese netizen has been affected by the digital media outlets ? Addressing these questions could assist to enhance mutual relation, narrowing mutual misunderstandings and correcting disinformation. It is found that Chinese netizens understand Nepal as an underdeveloped but culturally rich and lively country that reflects Chinese society and life before the beginning of the 21st century. The research contributes in the discourse of China-Nepal people-to-people relation, digital media studies and sociological studies highlighting how the new media can be used as the data sources to study the contemporary social trend.